Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s12877-016-0308-0
|View full text |Cite
|
Sign up to set email alerts
|

Parenting style, resilience, and mental health of community-dwelling elderly adults in China

Abstract: BackgroundGiven the increasing elderly population worldwide, the identification of potential determinants of successful ageing is important. Many studies have shown that parenting style and mental resilience may influence mental health; however, little is known about the psychological mechanisms that underpin this relationship. The current study sought to explore the relationships among mental resilience, perceptions of parents’ parenting style, and depression and anxiety among community-dwelling elderly adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 31 publications
6
46
1
3
Order By: Relevance
“…Conversely, if parents communicate with their children in a refusing way, it might impede the development of Zhongyong thinking, leading to emotional distress. These results were also in line with previous reports which implied that parenting styles might influence adult's emotional distress indirectly through their associations with personality traits, such as self-control (Hong and Cui, 2020) and resilience (Zhong et al, 2016). The mediating effect of Zhongyong thinking could be partially accounted for as follows.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Conversely, if parents communicate with their children in a refusing way, it might impede the development of Zhongyong thinking, leading to emotional distress. These results were also in line with previous reports which implied that parenting styles might influence adult's emotional distress indirectly through their associations with personality traits, such as self-control (Hong and Cui, 2020) and resilience (Zhong et al, 2016). The mediating effect of Zhongyong thinking could be partially accounted for as follows.…”
Section: Discussionsupporting
confidence: 91%
“…Congruent with previous research (Gao et al, 2012;Zhong et al, 2016;Cui, 2017), we found a positive association of parental rejection and overprotection with depression and anxiety symptoms and a negative association of parental warmth with depression and anxiety among adult college students. It is also consistent with a meta-analytic review of the link between parenting styles and both depressive and anxiety symptoms among adolescents that concluded that less parental warmth and over-involvement were linked with increased risks of depression and anxiety (Yap et al, 2014).…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…14,20,22,24 Fica evidente como a qualidade das relações é proporcional à satisfação, sendo em diversos contextos o motivo de melhora na saúde mental dos idosos. 18,25,15,14 Relações familiares mais atenciosas podem ser associadas com menor ocorrência de ansiedade e transtornos de humor, além de levar a comportamentos de saúde mais positivos. 18,20 Em contrapartida, relações familiares negativas podem ser arroladas com piora da saúde mental, sendo a ansiedade o transtorno mais demonstrado nesses casos.…”
Section: Métodounclassified
“…It is then observed that being resilient increases the likelihood of talking to health professionals about depressive symptoms and seeking healthcare to alleviate these symptoms, in addition to affecting health and well-being, which are other important aspects of physical and psychological adjustment and adaptation of older adults during the aging process. 19 The experience of aging is heterogeneous and can occur in different ways due to its own insertion in the different historical and social contexts. During the development of a disease, which is usually chronic at this stage, intellectual factors and the personality of the individuals will influence the perception and determine how each one "faces" this stage of life, favoring a resilient behavior or not.…”
Section: Original Articlementioning
confidence: 99%